PENGARUH POLA LATIHAN FOREHAND OVERHEAD CLEAR TERHADAP KEMAMPUAN TEKNIK PUKULAN LOB BULUTANGKIS PADA PESERTA EKSTRAKURIKULER SMAN 4 MALANG - Taufiq Nur Rachman; Supriyadi Supriyadi; Mulyani Surendra (Jurnal Sport Science, 2018)
Abstract: The lob stroke technique is an important blow to the quality of an athlete's game, in every blow that is launched and also in the overall effectiveness of the game strategy. As in the extracurricular badminton SMA N 4 Malang. This research aims to determine the effect of forehand overhead exercise pattern against ability technique lob badminton stroke on extracurricular participants Senior High School 4 Malang. After doing treatment in the form of variation of exercise model for 16 meetings. Based on the results of pretest data and postest data that have been analyzed using Statistical Package for Social Science is known significance value of 0.046 which means Ho is rejected. It can be concluded that the pattern of forehand overhead clearance exercise has an effect on the ability of badminton lob technique on extracurricular badminton participants of Senior High School 4 Malang. Keywords: badminton, forehand overhead clear, exercise model, lob stroke.Abstrak: Teknik pukulan lob merupakan pukulan yang penting dalam kualitas permainan seorang atlet, dalam setiap pukulan yang diluncurkan dan juga dalam efektivitas strategi permainan secara keseluruhan. Seperti halnya pada ekstrakurikuler bulutangkis SMA N 4 Malang. Penelitian ini bertujuan untuk mengetahui Pengaruh Pola Latihan Forehand Overhead Clear terhadap Kemampuan Teknik Pukulan Lob Bulutangkis pada Peserta Ekstrakurikuler SMAN 4 Kota Malang. Setelah dilakukan perlakuan berupa variasi model latihan selama 16 pertemuan. Berdasarkan hasil data pretes dan data postes yang telah dianalisis mengunakan Statistical Package for Social Science (SPSS) diketahui nilai signifikansi sebesar 0,046 yang berarti Ho ditolak. Dapat disimpulkan bahwa pola latihan forehand overhead clear berpengaruh terhadap kemampuan teknik pukulan lob bulutangkis pada peserta ekstrakurikuler bulutangkis SMAN 4 Malang. Kata Kunci: Bulutangkis, forehand overhead clear, model latihan, pukulan lob.